2012
DOI: 10.2975/35.3.2012.219.229
|View full text |Cite
|
Sign up to set email alerts
|

Community participation as a predictor of recovery-oriented outcomes among emerging and mature adults with mental illnesses.

Abstract: The higher scores on the dependent variables may be explained by younger adults having greater hope and higher expectations that are typical for those at that stage of life and that living longer with a serious mental illness and being exposed longer to the mental health system may dampen hope. Participation in general, and specific areas of participation, were predictive of recovery-oriented outcomes. These results should inspire future developmentally-oriented research examining factors that facilitate recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 17 publications
2
64
0
2
Order By: Relevance
“…Younger adults with schizophrenia tend to be more hopeful and have greater expectations than those who have lived longer with a diagnosis of schizophrenia; the younger adults are not yet worn down by the effects of their illness (Kaplan, Salzar, & Brusilovskiy, 2012). By using the definitions of happiness found in this study, paired with the young adult’s experiences and needs, psychiatric nurses can help these young adults focus on overcoming the barriers to happiness that would lead to a poor quality of life.…”
Section: Conclusion and Implications For Nursing Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Younger adults with schizophrenia tend to be more hopeful and have greater expectations than those who have lived longer with a diagnosis of schizophrenia; the younger adults are not yet worn down by the effects of their illness (Kaplan, Salzar, & Brusilovskiy, 2012). By using the definitions of happiness found in this study, paired with the young adult’s experiences and needs, psychiatric nurses can help these young adults focus on overcoming the barriers to happiness that would lead to a poor quality of life.…”
Section: Conclusion and Implications For Nursing Practicementioning
confidence: 99%
“…By using the definitions of happiness found in this study, paired with the young adult’s experiences and needs, psychiatric nurses can help these young adults focus on overcoming the barriers to happiness that would lead to a poor quality of life. Efforts to engage these young adults to improve their experience of happiness and quality of life may provide the framework needed to sustain hope as they age leading to recovery (Kaplan, Salzar, & Brusilovskiy, 2012). …”
Section: Conclusion and Implications For Nursing Practicementioning
confidence: 99%
“…Furthermore, Kaplan et al. () found that components of participation such as civic engagement, friendship, group membership, and employment were positively associated with greater recovery and quality of life. Additionally, participants who established casual relationships with a larger number of community members, such as store employees and wait staff, had stronger perceptions of belonging and overall life satisfaction (Wieland, Rosenstock, Kelsey, Ganguli, & Wisniewski, ).…”
Section: Introductionmentioning
confidence: 99%
“…People with psychiatric disabilities and criminal records who return to community life can also become a more visible and active part of the consumer self-help movement, drawing on that movement’s lessons with regard to successful policy advocacy, the ongoing push for programs that promote community inclusion rather than isolation (Kaplan, Salzer, & Brusilovskiy, 2012) and the creation of jobs within the mental health and criminal justice systems for consumers. Engagement in advocacy, community life, and social service positions has taught an emerging generation of individuals with only psychiatric disabilities about their own capacity for jobs and justice, and can do the same for this population as well.…”
Section: Resultsmentioning
confidence: 99%